2016
DOI: 10.1177/0018720816644083
|View full text |Cite
|
Sign up to set email alerts
|

External Hand Forces Exerted by Long-Term Care Staff to Push Floor-Based Lifts

Abstract: Results may help to address risk of work-related musculoskeletal injury, especially in locations with novel compliant flooring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Focus group findings (sample size not reported) revealed that compliant flooring (Kradal, 1.20 cm) increased subjective ratings of leg fatigue for LTC nurses and difficulty when maneuvering equipment when compared to standard flooring (vinyl, linoleum, tile) [ 89 ]. In addition, six other records noted increased subjective ratings of perceived fatigue when maneuvering equipment, including beds [ 51 , 61 , 87 , 89 , 92 , 93 ], wheelchairs [ 51 , 89 , 93 ], stretchers [ 92 , 93 ], and floor-based lifts [ 51 , 61 , 87 , 89 , 94 ] over both carpet (n = 3 records) and NCF (n = 4 records) in acute and LTC settings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Focus group findings (sample size not reported) revealed that compliant flooring (Kradal, 1.20 cm) increased subjective ratings of leg fatigue for LTC nurses and difficulty when maneuvering equipment when compared to standard flooring (vinyl, linoleum, tile) [ 89 ]. In addition, six other records noted increased subjective ratings of perceived fatigue when maneuvering equipment, including beds [ 51 , 61 , 87 , 89 , 92 , 93 ], wheelchairs [ 51 , 89 , 93 ], stretchers [ 92 , 93 ], and floor-based lifts [ 51 , 61 , 87 , 89 , 94 ] over both carpet (n = 3 records) and NCF (n = 4 records) in acute and LTC settings.…”
Section: Resultsmentioning
confidence: 99%
“…Eight records revealed that carpet and NCFs increase the forces required to maneuver (push, pull, and/or turn) carts [ 84 86 ], beds/patient trolleys [ 90 ], wheelchairs [ 28 , 65 ], and floor-based lifts [ 90 , 91 , 94 ]. When considering recommended limits to safely maneuver equipment, 3 (of 6) records that examined carpet [ 86 , 91 , 94 ] and 2 (of 3) records that examined NCF [ 90 , 94 ] recorded values that were over the recommended limits, suggesting an increased risk for injury. Keeping the forces required to move equipment within recommended limits is essential to prevent injury, as indicated by one record which documented 5 adverse events from staff working on a NCF in a 16 month period, including 1 lower back muscle strain while moving a patient on a trolley (Tarkett Omnisport Excel, 0.83 cm) [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst the proposed testing method is written in the context of hip protector assessment, here we have used it as a novel basis for comparing flooring products, with a view to extending further standardization to this field. A hospital-based pilot study of shock-absorbing flooring for fall-related injury prevention indicated that the intervention has promising features with regards to potential for injury prevention (yet to be verified by a definitive trial) [32]; however, adverse effects may be present for staff having to wheel heavy objects across the floor, with risk particularly increased in instances where staff are handling equipment in isolation [33][34] [35]. There is an important assessment to be made therefore, when selecting a shock-absorbing flooring product, to understand the potential trade-off between impact force reduction and horizontal pulling force required to move wheeled objects.…”
Section: Introductionmentioning
confidence: 99%